A Synopsis of Bioacoustic Studies of Anuran Amphibians of Borneo - Das, Indraneil; Sukumaran, Jeet; Haas, Alexander (Society for the Study of Amphibians and Reptiles, 2006)
We summarize information on acoustics recorded from the anuran amphibians of Borneo. Currently, 154 species of frogs and toads (Amphibia: Anura) are known from Borneo (Das 2005; Das and Haas 2005; Inger and Stuebing 2005). The five species of Ichthyophiidae known from Borneo presumably do not call. The quality of acoustic information of Bornean amphibians reported in the literature varies significantly. In this review, we scored call data from 0–5, where 0 = unknown; 1 = abbreviated, onomatopoeic or verbal description; 2 = analytical description only, no sonogram/oscillogram; 3 = sonogram/oscillogram only, no analytical description; 4 = sonogram/oscillogram and analytical description; and 5 = recording on a CD.